(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
Finance is the lifeline of any form of business, and its timely and adequate supply is crucial for the survival of micro and small enterprises. Micro, small and medium enterprises (MSMES) play a crucial role in the development of our economy by providing ample scope of employment, export promotions, uplifting regional balance and contribution toward GDP. Despite of the noticeable achievements, this sector faces challenges for timely and adequate supply of finance. State government always promotes these sectors with different schemes and policies by collaborating with financial institutions from time to time. This paper deals with understanding the support of financial institutions in the study area provided to the micro and small enterprises for accessing finance i,e analysing the banking institutions in the papum pare district of Arunachal Pradesh for providing loans to the micro and small enterprises.